Biomineralized MnO2 Nanoparticle-Constituted Hydrogels Promote Spinal Cord Injury Repair by Modulating Redox Microenvironment and Inhibiting Ferroptosis - Yuyu Sun; Jinlong Zhang; Yong Gu; Tianqing Liu; Liang Chen (MDPI AG, 2024)
Spinal cord injury (SCI) is one of the most severe injuries, characterized by multiple positive feedback regulatory signaling networks formed by oxidative stress and inflammation in the injury microenvironment, leading to neuronal cell damage and even death. Here, astragaloside IV (AS), known for its regulatory role in ferroptosis, was encapsulated in the cavity of apoferritin (HFn) after an in situ biomineralization process involving MnO2, resulting in the synthesis of HFn@MnO2/AS nanoparticles. These nanoparticles were then dispersed in chitosan/polyvinyl alcohol/glutaraldehyde/sodium β-glycerophosphate (CGPG) hydrogels to form CGPG-HFn@MnO2/AS injectable thermosensitive hydrogels that can scavenge reactive oxygen species (ROS) in the microenvironment. Our findings indicated that the prepared CGPG-HFn@MnO2/AS hydrogel exhibited remarkable efficacy in scavenging ROS in vitro, effectively ameliorating the oxidative stress microenvironment post-SCI. Furthermore, it inhibited oxidative stress-induced ferroptosis in vitro and in vivo by regulating SIRT1 signaling, thereby promoting neuronal cell migration and repair. Hence, the developed hydrogel combining MnO2 and AS exhibited multifaceted abilities to modulate the pathological microenvironment, providing a promising therapeutic strategy for central nervous system (CNS) diseases.